Princess diaries 2 : royal engagement - Marshall, Garry (Pasig City : Viva Video, 2004)
Starring the irresistible Anne Hathaway (Ella Enchanted) and Academy Awards winner Julie Andrews ( Best Actress, Mary Poppins, 1964), this modern-day fairy tale picks up right where The Princess Diaries left off! As future queen of Ganovia, Princess Mia ( Hathaway) has everything a girl could want-except the magical romance she's always dreamed of. But soon, Mia's shocked to discover that she needs to get married right now or her family will lose the crown! Comic complications rules the day in this delightful family story about finding out who you really are and discovering what it takes to make your dreams come true!